Risk assessment of sodium cyclamate and acesulfame in foods in Hubei Province - ZHAO Yunxia; LIU Bing; WANG Yi; NIU Lin; WANG Shuo (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo analyze the risk of food additives in Hubei Province, provide a basis for relevant departments to formulate management measures, and reduce the potential risk.MethodsIn the paper, the crystal ball software and Monte Carlo simulation method were used to evaluate the average daily exposure and risk probability of sodium cyclamate and acesulfame in foods in Hubei Province.ResultsThe average daily exposure and risk entropy of sodium cyclamate in pickled vegetable products were the highest, which were 3.98E-4 g/kg BW/d and 0.0372, respectively. In addition, there are significant differences in the risk probability of additives in different foods. The risk probability ranking of acesulfame in foods was pickled vegetable products > canned > beverage > pastry, and that of sodium cyclamate was pickled products > beverage > pastry > canned food.ConclusionThe health risk of residents in Hubei Province who ingest two sweeteners through diet was generally low, and the risk of sodium cyclamate was slightly higher than that of acesulfame, both at an acceptable level.